Wzięcie udziału przez prokuratora w postępowaniu cywilnym jako gwarancja zapewnienia efektywności ochrony prawnej - Misztal-Konecka, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The role of the prosecutor in the legal system is traditionally perceived in the context of performing tasks relating to the prosecution of offences and upholding the rule of law. It is worth mentioning, however, that pursuant to Article 7 sentence 1 of the Code of Civil Procedure the prosecutor may petition to institute proceedings in any civil matter as well as participate in any pending proceedings if he considers his presence necessary to protect the rule of law, citizens’ rights or social interest. While the broad competence range of the prosecutor in civil proceedings has been assessed with high criticism in the literature on numerous occasions, it is with great caution that one should view possible tendencies towards exclusion of the prosecutor as an attendant of proceedings, without affiliation to either party, when the public interest calls for their participation. Especially in the cases where the court notifies the prosecutor of the need to participate in proceedings, one ought to conclude that it is the moment when the principle of effective legal protection becomes most fully realized through equalizing the litigious position of the parties and prevention of the occurrence of a defect which might invalidate the proceedings. The author postulates transforming notification of the need to participate in proceedings served on the prosecutor into summoning for attending it.